AN ANALYSIS OF DEIXIS IN "BEST SONG EVER" LYRICS BY ONE DIRECTION - Khafidoh Hidayati (ETNOLINGUAL, 2021)
AbstractThis study aims to analysis and identify the deixis contained in the song "Best Song Ever" by One Direction. The research subjects of the study are song lyrics “Best Song Ever” by One Direction. The researcher analyzed each lyric verse in the song "Best Song Ever" by One Direction to make it easier to do this research. The researcher collected data s deixis in song lyrics “Best Song Ever” by One Direction, after that the research analysis deixis in song lyrics “Best Song Ever” by One Direction and category the types of deixis in song lyrics “Best Song Ever” by One Direction, the research using qualitative method. In this study, the author has analyzed a song entitled "Best Dong Ever by One Direction" and found several types of deixis errors that often appear in each verse of the song's lyrics, namely person deixis and temporal/time deixis using qualitative research methods. The dominant deixis in the lyric song “Best Song Ever” by One Direction is person Deixis. Keywords: deixis, song, lyric AbstrakPenelitian ini bertujuan untuk menganalisis dan mengidentifikasi deiksis yang terdapat dalam lagu “Best Song Ever” oleh One Direction. Subjek penelitian dari penelitian ini adalah lirik lagu “Best Song Ever” oleh One Direction. Peneliti menganalisis setiap syair lirik dalam lagu “Best Song Ever” oleh One Direction untuk mempermudah dalam melakukan penelitian ini. Peneliti mengumpulkan data deiksis dalam lirik lagu “Best Song Ever” oleh One Direction, setelah itu penelitian menganalisis deiksis dalam lirik lagu “Best Song Ever” oleh One Direction dan mengkategorikan jenis-jenis deiksis dalam lirik lagu “Best Song Ever” oleh One Direction, penelitian ini menggunakan metode kualitatif. Dalam penelitian ini, penulis telah menganalisis sebuah lagu yang berjudul “Best Song Ever” by One Direction dan menemukan beberapa jenis kesalahan deiksis yang sering muncul pada setiap bait lirik lagu tersebut, yaitu deiksis persona dan deiksis temporal/waktu dengan menggunakan metode penelitian kualitatif. Deiksis yang dominan dalam lirik lagu “Best Song Ever” oleh One Direction adalah deiksis persona. Kata Kunci: deiksis, lagu, lirik